2005
DOI: 10.1182/blood-2005-01-0240
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the basis for the properties of fibrin produced from fibrinogen-containing γ′ chains

Abstract: Human fibrinogen 1 is homodimeric with respect to its ␥ chains ('␥ A -␥ A '), whereas fibrinogen 2 molecules each contain one ␥ A (␥ A 1-411V) and one ␥ chain, which differ by containing a unique C-terminal sequence from ␥408 to 427L that binds thrombin and factor XIII. We investigated the structural and functional features of these fibrins and made several observations. First, thrombin-treated fibrinogen 2 produced finer, more branched clot networks than did fibrin 1. These known differences in network struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 65 publications
11
89
1
Order By: Relevance
“…68 Their data further suggested that FXIII activation was slower in the presence of ␥A/␥Ј fibrinogen than it was in the presence of ␥A/␥A fibrinogen. 30 FXIII activation peptide cleavage by Atroxin, a snake venom enzyme that cleaves FpA from fibrinogen but does not bind to the ␥Ј chain, was not affected by the presence of ␥A/␥Ј fibrinogen, suggesting that the observed rate differences in the thrombin-catalyzed system were related to thrombin binding to the ␥Ј chain.…”
Section: Fxiii Binding and Fibrinogen Cross-linkingmentioning
confidence: 97%
See 2 more Smart Citations
“…68 Their data further suggested that FXIII activation was slower in the presence of ␥A/␥Ј fibrinogen than it was in the presence of ␥A/␥A fibrinogen. 30 FXIII activation peptide cleavage by Atroxin, a snake venom enzyme that cleaves FpA from fibrinogen but does not bind to the ␥Ј chain, was not affected by the presence of ␥A/␥Ј fibrinogen, suggesting that the observed rate differences in the thrombin-catalyzed system were related to thrombin binding to the ␥Ј chain.…”
Section: Fxiii Binding and Fibrinogen Cross-linkingmentioning
confidence: 97%
“…31 It has been suggested that allosteric effects of the binding of the ␥Ј chain to exosite II on the thrombin catalytic site may be responsible for the inhibitory activity of ␥A/␥Ј fibrinogen. 30 Recent reports suggest that the ␥Ј chain may also function as a reservoir for active thrombin in the fibrin clot. Thrombin bound to fibrin was shown to remain functionally active.…”
Section: Thrombin Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…58,59 Thrombin interacts with the carboxy terminal sequence of the ␥Ј chain through its exosite 2, 26,27,57 which prevents the participation of this exosite in the binding of thrombin to heparin 60 and which recently was found to be responsible for the observation that thrombin-induced FPA generation was slower with ␥A/␥Ј fibrinogen than with ␥A/␥A fibrinogen. 61 Experiments in which thrombin generation was measured in afibrinogenemia plasma and fibrinogen-depleted plasma supplemented with ␥A/␥A fibrinogen or ␥A/␥Ј fibrinogen showed that ␥A/␥Ј fibrinogen had a more profound effect in down-regulating thrombin generation than ␥A/␥A fibrinogen. 62 Future studies should reveal whether and how a 2-fold reduction of the ␥Ј/␥ ratio would influence fibrin formation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In order to clarify whether thrombin can still recognize the cleavage sites in the N-terminal region of fibrinogen to promote fibrinogenesis (Siebenlist et al, 2005), RCC-treated fibrinogen was incubated with thrombin and aliquots were examined by MALDI-TOF mass spectrometry. Cleavage of fibrinogen releases fibrinopeptide A and B, peptides of ∼1900 Da and ∼2400 Da in length.…”
Section: Disruption Of Fibrinogenesis In the Presence Of Rccsmentioning
confidence: 99%